Evaluación de los sistemas informáticos de gestión académica basado en la norma iso 25010 en la ESPAM MFL del cantón Bolívar - Díaz Encarnación, Mónica Lissette (2017)
The present investigation was carried out with the purpose of evaluating the quality of the computer systems of academic management of the Software Production Unit (UPS) of the Computing career of ESPAM MFL. In the study objective, the surveys were used as referring to the ISO / IEC 25010 standard, to know the perspective of the work team, the teachers and students and to carry out a statistical analysis. The interview technique was used to know the systems to be evaluated (9 systems), and the market research methodology consists of 7 phases: problem formulation, to define the research objective; determination of the design, being chosen the exploratory design that allowed to make an analysis of the information; preparation of the investigation, through the collection of information and design of the sheet according to the chosen standard to verify if it complies with what is recommended by it; fieldwork, the systems to be evaluated were established; processing of information, by reviewing the questionnaires applied and their metric valuation; exploration and analysis, the development of tables and graphs with their respective analyzes; communication of the report, which presented the results obtained through which the level of acceptance and quality of the systems could be known, complemented by ISO / IEC 14598, which indicates that the systems are in a satisfactory level and finally the improvement plan for each system was proposed.